Bulk heterojunction polymer memory devices with reduced graphene oxide as electrodes - Liu, Juqing (2012)
A unique device structure with a configuration of reduced graphene oxide (rGO) /P3HT:PCBM/Al has been designed for the polymer nonvolatile memory device. The current−voltage (I−V) characteristics of the fabricated device showed the electrical bistability with a write-once-read-many-times (WORM) memory effect. The memory device exhibits a high ON/OFF ratio (104−105) and low switching threshold voltage (0.5−1.2 V), which are dependent on the sheet resistance of rGO electrode. Our experimental results confirm that the carrier transport mechanisms in the OFF and ON states are dominated by the thermionic emission current and ohmic current, respectively. The polarization of PCBM domains and the localized internal electrical field formed among the adjacent domains are proposed to explain the electrical transition of the memory device.